Immunotherapy of hepatocellular carcinoma: recent progress and new strategy - Li, Jiarui; Xuan, Shihai; Dong, Peng; Xiang, Ze; Gao, Ce; Li, Mo; Huang, Lan; Wu, Jian (Frontiers in Immunology, 2023)
Due to its widespread occurrence and high mortality rate, hepatocellular carcinoma (HCC) is an abhorrent kind of cancer. Immunotherapy is a hot spot in the field of cancer treatment, represented by immune checkpoint inhibitors (ICIs), which aim to improve the immune system’s ability to recognize, target and eliminate cancer cells. The composition of the HCC immune microenvironment is the result of the interaction of immunosuppressive cells, immune effector cells, cytokine environment, and tumor cell intrinsic signaling pathway, and immunotherapy with strong anti-tumor immunity has received more and more research attention due to the limited responsiveness of HCC to ICI monotherapy. There is evidence of an organic combination of radiotherapy, chemotherapy, anti-angiogenic agents and ICI catering to the unmet medical needs of HCC. Moreover, immunotherapies such as adoptive cellular therapy (ACT), cancer vaccines and cytokines also show encouraging efficacy. It can significantly improve the ability of the immune system to eradicate tumor cells. This article reviews the role of immunotherapy in HCC, hoping to improve the effect of immunotherapy and develop personalized treatment regimens.